The dissemination of pelvic limb nerves originating from the lumbosacral plexus in the porcupine (Hystrix cristata) - Aydin, A. (Czech Academy Agricultural Sciences, 2009)
In this study the nerves originating from the plexus lumbosacrales of porcupines (Hystrix cristata) were investigated. Four porcupines (two males and two females) were used. The plexus lumbosacrales of animals were appropriately dissected and dissemination of pelvic limb nerves originating from the plexus lumbosacrales was examined. The nerves originated from the plexus lumbosacrales of porcupines (Hystrix cristata): iliohypogastric nerve from T15, ilioinguinal nerve (on the left side of only one animal) genitofemoral and lateral femoral cutaneous nerves from T15 and L1, the femoral and obturator nerves from T15, L1, L2 and L3. The femoral nerve divided into two as the common dorsal digital nerve I and II after it branched into motor and skin nerves. The cranial gluteal nerve originated from L3 and L4 in males and from only L3 in females. The caudal gluteal nerve and the caudal femoral cutaneous and sciatic nerves originated from the common root which was formed by the union of L3, L4 and S1 in one animal, and by the union of L3, L4, S1 and S2 in the three other animals. The sciatic nerve divided into the tibial and fibular nerve. The fibular nerve divided into two as the common dorsal digital nerve III and IV, and extended after branching in one direction to extensor muscles. The tibial nerve divided into the common palmares digital nerve I, II, III and IV, and extended after branching into the cutaneous surae caudales nerve and rami muscle distales. The cutaneous surae caudales nerve divided into the common palmar and dorsal digital nerve V. The pudendal and caudal rectal nerves originated from S2 in three animals and from S1 in the remaining animal. In the point of origin from the branches of spinal nerves originating from the plexus lumbosacrales, and also in the absence of the ilioinguinal nerve (on left side abroad of only one animal), originating from T15 and L1 of the genitofemoral and lateral femoral cutaneous nerves, from T15 of the iliohypogastric nerve, the studied porcupines differed from rodentia and other mammals
Keywords: lumbosacral plexus; dissemination; pelvic limb's nerves; posterior legs; porcupines (Hystrix cristata)